A Simple Single Specimen Method for Measuring the Fracture Surface Energy of Rubber Materials - Ait Hocine, N.; Na1t Abdelaziz, M. (Engineering Transactions, 2001)
In this investigation, particular attention is paid to the generalized theory of fracture mechanics developed by Andrews and based on the spatial strain energy density distribution W in the case of an infinite lamina. A numerical analysis using a finite element method brings out some serious shortcomings in the fundamental equation of this theory when dealing with laboratory specimens of finite dimensions. It is proven that the $J$ integral derived from this equation has no physical meaning. We have proposed an alternative expression of W which leads to a simplified $J$ integral requiring measurements on one specimen only.